A Reality of Man - Krakauskas, Edmundas (Problemos, 1998)
Almost four hundred years ago R. Descartes (1596-1650) argued cogito ergo sum. This argument has been analysed up to the present day and will continue to be analysed in the future. Is man real as a spiritual being or is he with two natures: material and spiritual? A man is not material (that is his body). The words man and body are not synonyms. Man is only real as a rational being; he is only an understandable phenomenon. The body is a phenomenon of sensation (that is, at the biological level). The argument for the material nature of man is impossible; in such a case the argument itself must be treated as a natural phenomenon.